Natural Course of Pediatric Portal Hypertension. Issue 9 (16th July 2020) - Kassam, Al‐Faraaz; Goddard, Gillian R.; Johnston, Michael E.; Cortez, Alexander R.; Trout, Andrew T.; Jenkins, Todd M.; Miethke, Alexander G.; Campbell, Kathleen M.; Bezerra, Jorge A.; Balistreri, William F.; Nathan, Jaimie D.; Alonso, Maria H.; et al.
Abstract : The etiology of portal hypertension (pHTN) in children differs from that of adults and may require different management strategies. We set out to review the etiology, management, and natural history of pHTN at a pediatric liver center. From 2008 to 2018, 151 children and adolescents with pHTN were identified at a free‐standing children's hospital. Patients were stratified by etiology of pHTN (intrahepatic disease [IH], defined as cholestatic disease and fibrotic or hepatocellular disease; extrahepatic disease [EH], defined as hepatic vein obstruction and prehepatic pHTN). Patients with EH were more likely to undergo an esophagoduodenscopy for a suspected gastrointestinal bleed (77% vs. 41%; P  < 0.01). Surgical interventions differed based on etiology ( P  < 0.01), with IH more likely resulting in a transplant only (65%) and EH more likely to result in a shunt only (43%); 30% of patients with IH and 47% of patients with EH did not undergo an intervention for pHTN. Kaplan‐Meier analysis revealed a significant increase in mortality in the group that received no intervention compared to shunt, transplant, or both and lower mortality in patients with prehepatic pHTN compared to other etiologies ( P  < 0.01 each). Multivariate analysis revealed increased odds of mortality in patients with refractory ascites (odds ratio [OR], 4.34; 95% confidence interval [CI], 1.00, 18.88; P  = 0.05) and growth failure (OR, 13.49; 95% CI, 3.07, 58.99; P  < 0.01). Conclusion: In this single institution study, patients with prehepatic pHTN had better survival and those who received no intervention had higher mortality than those who received an intervention. Early referral to specialized centers with experience managing these complex disease processes may allow for improved risk stratification and early intervention to improve outcomes. Abstract :